2015
DOI: 10.1016/j.pec.2015.02.018
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory typology of provider responses that encourage and discourage conversation about complementary and integrative medicine during routine oncology visits

Abstract: OBJECTIVE To characterize how providers respond to patient mentions of complementary and integrative medicine (CIM) during routine oncology visits. METHODS Ethnographic methods were used over a two and a half year period with 82 advanced cancer patients and their providers across four oncology clinics. Participant observation fieldnotes were analyzed using Discourse Analysis. RESULTS CIM was mentioned in 78/229 (34%) of the total observed visits. Patients initiated talk about CIM (76%) more than providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 42 publications
3
21
1
2
Order By: Relevance
“…Others have found that half to three quarters of CAM discussions were initiated by patients . In our study, the UM and SoCal university settings showed patients raising the topic in 61% and 71% of instances, respectively.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Others have found that half to three quarters of CAM discussions were initiated by patients . In our study, the UM and SoCal university settings showed patients raising the topic in 61% and 71% of instances, respectively.…”
Section: Discussionsupporting
confidence: 42%
“…A single‐center study in Australia suggested that 24%–29% of oncology visits contained a CAM discussion . Koenig found that 34% of visits at one center in San Francisco included CAM discussion . Yet CAM use may vary by racial and ethnic subgroups as well as region and care setting .…”
Section: Introductionmentioning
confidence: 99%
“…In a setting of increasing demand from patients, there is currently a need to bridge the gap between conventional medicine and complementary medicines within a secure framework that allows for open discussion between the physician and their patients (Frenkel, Ben‐Arye, & Cohen, 2010; Ge et al., 2013; Koenig, Ho, Trupin, & Dohan, 2015; Stub et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As Koenig et al [52] point out there are ways in which providers can promote communication about CAM and traditional remedies with patients, without necessarily endorsing the use of such products. Healthcare providers should be well informed about the kinds of products that patients may be accessing so that they can counsel patients regarding the concurrent use of these medicines with prescribed regimens and empower patients to make appropriate decisions in this regard.…”
Section: Discussionmentioning
confidence: 99%